Is “ai” a Unitary or Separate Morpheme? - Fáladé Ọpéyemí Williams (Britain International for Academic Research (BIAR-Publisher), 2023)
Yorubá is one of the major languages spoken in Nigeria alongside Hausa and Igbo. It has enjoyed extensive research works from both native and non-native authors in virtually all the sub-fields of linguistics. However, there are areas of disagreement among scholars, one of which is the status of the negative maker